THE EFFECT OF AIR FLOW RATE ON THE CHARACTERISTICS OF PULVERIZED CATALYTIC COMBUSTION OF RICE HUSK WASTE BIOMASS - Hamidi, Nurkholis; Yuliati, Lilis; Purnami; Maulana , Syahrizal (Jurnal Rekayasa Mesin, 2025)
The purpose of this study was to determine the effect of airflow rate on the characteristics of catalytic combustion of pulverized rice husk biomass. Natural zeolite was used as the catalyst in this study. The combustion characteristics included the value of Initiation Temperature of Volatile Matter (ITVM), Initiation Temperature of Fixed Carbon (ITFC), peak of weight loss rate temperature (PT), Burning out Temperature (BT), mass reduction graph (TGA), mass reduction rate (DTG), heating value, and activation energy were measured. The sample used was 45-200 µm in size, and the percentage of catalyst was 7%. The research was carried out using 4 variations, including 2.9 ml/min, 5.8 ml/min, 9.0 ml/min, and 14.8 ml/min, each of which contains the same air composition, namely 80% nitrogen and 20% oxygen. The results showed that the greater the airflow contained in the pulverized biomass catalytic combustion process could increase the combustion characteristics including reducing the value of ITFC, PT, and BT. In addition, it also accelerates the rate of mass reduction and decreases its activation energy due to increasing pressure along with increasing temperature in the combustion chamber, besides that excess air also causes the combustion that occurs in more perfect combustion.